(x-3).6(x+1)=65

Simple and best practice solution for (x-3).6(x+1)=65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3).6(x+1)=65 equation:


Simplifying
(x + -3) * 0.6(x + 1) = 65

Reorder the terms:
(-3 + x) * 0.6(x + 1) = 65

Reorder the terms:
(-3 + x) * 0.6(1 + x) = 65

Reorder the terms for easier multiplication:
0.6(-3 + x)(1 + x) = 65

Multiply (-3 + x) * (1 + x)
0.6(-3(1 + x) + x(1 + x)) = 65
0.6((1 * -3 + x * -3) + x(1 + x)) = 65
0.6((-3 + -3x) + x(1 + x)) = 65
0.6(-3 + -3x + (1 * x + x * x)) = 65
0.6(-3 + -3x + (1x + x2)) = 65

Combine like terms: -3x + 1x = -2x
0.6(-3 + -2x + x2) = 65
(-3 * 0.6 + -2x * 0.6 + x2 * 0.6) = 65
(-1.8 + -1.2x + 0.6x2) = 65

Solving
-1.8 + -1.2x + 0.6x2 = 65

Solving for variable 'x'.

Reorder the terms:
-1.8 + -65 + -1.2x + 0.6x2 = 65 + -65

Combine like terms: -1.8 + -65 = -66.8
-66.8 + -1.2x + 0.6x2 = 65 + -65

Combine like terms: 65 + -65 = 0
-66.8 + -1.2x + 0.6x2 = 0

Begin completing the square.  Divide all terms by
0.6 the coefficient of the squared term: 

Divide each side by '0.6'.
-111.3333333 + -2x + x2 = 0

Move the constant term to the right:

Add '111.3333333' to each side of the equation.
-111.3333333 + -2x + 111.3333333 + x2 = 0 + 111.3333333

Reorder the terms:
-111.3333333 + 111.3333333 + -2x + x2 = 0 + 111.3333333

Combine like terms: -111.3333333 + 111.3333333 = 0.0000000
0.0000000 + -2x + x2 = 0 + 111.3333333
-2x + x2 = 0 + 111.3333333

Combine like terms: 0 + 111.3333333 = 111.3333333
-2x + x2 = 111.3333333

The x term is -2x.  Take half its coefficient (-1).
Square it (1) and add it to both sides.

Add '1' to each side of the equation.
-2x + 1 + x2 = 111.3333333 + 1

Reorder the terms:
1 + -2x + x2 = 111.3333333 + 1

Combine like terms: 111.3333333 + 1 = 112.3333333
1 + -2x + x2 = 112.3333333

Factor a perfect square on the left side:
(x + -1)(x + -1) = 112.3333333

Calculate the square root of the right side: 10.598742062

Break this problem into two subproblems by setting 
(x + -1) equal to 10.598742062 and -10.598742062.

Subproblem 1

x + -1 = 10.598742062 Simplifying x + -1 = 10.598742062 Reorder the terms: -1 + x = 10.598742062 Solving -1 + x = 10.598742062 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 10.598742062 + 1 Combine like terms: -1 + 1 = 0 0 + x = 10.598742062 + 1 x = 10.598742062 + 1 Combine like terms: 10.598742062 + 1 = 11.598742062 x = 11.598742062 Simplifying x = 11.598742062

Subproblem 2

x + -1 = -10.598742062 Simplifying x + -1 = -10.598742062 Reorder the terms: -1 + x = -10.598742062 Solving -1 + x = -10.598742062 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = -10.598742062 + 1 Combine like terms: -1 + 1 = 0 0 + x = -10.598742062 + 1 x = -10.598742062 + 1 Combine like terms: -10.598742062 + 1 = -9.598742062 x = -9.598742062 Simplifying x = -9.598742062

Solution

The solution to the problem is based on the solutions from the subproblems. x = {11.598742062, -9.598742062}

See similar equations:

| 9+(-2)=4+t | | 7x+1=31+4x | | 0.60x+.05(4-x)=.10(-20) | | 3(2x+6)=-6 | | 2m-9-8m=27 | | 6-2(4-8x)=2(3x-5) | | 2.5=d-(20) | | x-(3x+7)=11 | | x-6=-12+2x | | 2.5=d-(.20) | | -9+5x=-5x+1 | | 6.8x-15.3+4.2x=6.4+12x | | b=85+(23)w | | x+8=5x+52 | | 7x+19+-2x=55 | | -3x-5=-47+4x | | 5m-2(4m-1)=-14 | | 10=3x-5x+6 | | x-5-8x=16 | | -14x-4(2x-5)=9 | | -x+6+2x=13 | | 18=8-6b | | (30+5x)+(10x+15)=180 | | (x+6)(3x+8)=0 | | -1-5x+3x=1 | | y-5-2=10 | | 12x-13+8=2x | | 4=x+x+2 | | 12x+4-26=-2(3x-82) | | 2y-6x-4=0 | | 10w+5-3w=40 | | 7x-(2x-12)=-8 |

Equations solver categories